2019
DOI: 10.1002/jmd2.12067
|View full text |Cite
|
Sign up to set email alerts
|

Clinical findings in Brazilian patients with adult GM1 gangliosidosis

Abstract: GM1 gangliosidosis is a lysosomal storage disorder caused by β‐galactosidase deficiency. To date, prospective studies for GM1 gangliosidosis are not available, and only a few have focused on the adult form. This retrospective cross‐sectional study focused on clinical findings in Brazilian patients with the adult form of GM1 gangliosidosis collected over 2 years. Ten subjects were included in the study. Eight were males and two females, with median age at diagnosis of 11.5 years (IQR, 4‐34 years). Short stature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…We describe 17 individuals diagnosed with GLB1 deficiency presenting with various degrees and combinations of dysostosis multiplex and neurologic/neurocognitive dysfunction. Ten of the 17 patients (P1, 2,7,8,9,10,12, 15,16,17) were described previously in the context of clinical findings in adult GM1 gangliosidosis 9 …”
Section: Resultsmentioning
confidence: 99%
“…We describe 17 individuals diagnosed with GLB1 deficiency presenting with various degrees and combinations of dysostosis multiplex and neurologic/neurocognitive dysfunction. Ten of the 17 patients (P1, 2,7,8,9,10,12, 15,16,17) were described previously in the context of clinical findings in adult GM1 gangliosidosis 9 …”
Section: Resultsmentioning
confidence: 99%
“…Although cohort studies have been reported in other countries, [5][6][7][8] there has never been a large cohort study in France. Published reports provide descriptions of symptom prevalence but data on the age of symptom onset and disease progression are generally not reported.…”
Section: Introductionmentioning
confidence: 99%
“…The incidence of the disease in the European country of Malta is 1 case per 3700 live births 7 . In terms of race, Brazil has the highest frequency 8,9 and the disease has also been found in the Japanese, 10 Nigerian infantiles, 11 and Colombia 12 . A study by Georgiou et al found that the disease was also observed in Cypriot populations 13 .…”
Section: Introductionmentioning
confidence: 99%
“…Type III or adults occur from the early third year to the late thirties. In this variant, patients have abnormal and involuntary movements and the following symptoms are observed: dysarthria, Facial dystonia, Parkinsonian features, Ataxia, 24 Weak CNS involvement, Reduce skeletal changes, and so on 8,27,28 . In this case, the mortality varies from person to person.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation